2017
DOI: 10.1016/j.ijrobp.2017.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy for Early-Stage Breast Cancer Using a Robotic Linear Accelerator

Abstract: Conclusion: In this study, we reported the largest series of palliative breast radiation. Palliative RT for breast tumor is an effective treatment for pain, bleeding, ulceration, discharge, and discomfort. 8 Gy in a single fraction can be effective treatment for massive bleeding or sever pain; however, fractionated radiation provides robust, durable response with minimal toxicity. Literature regarding palliative RT to the breast is scarce and prospective protocols are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With advancements in high-precision radiotherapy techniques, stereotactic body radiation therapy has become an emerging option for early breast cancer, in the form of stereotactic A-PBI (S-PBI). Several Western institutions have shown that S-PBI is a safe and feasible treatment in patients with early breast cancer who meet strict criteria (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…With advancements in high-precision radiotherapy techniques, stereotactic body radiation therapy has become an emerging option for early breast cancer, in the form of stereotactic A-PBI (S-PBI). Several Western institutions have shown that S-PBI is a safe and feasible treatment in patients with early breast cancer who meet strict criteria (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%